1992
DOI: 10.1080/07315724.1992.10737987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Changes and Early Nutrition on Cholesterol Metabolism in Infancy: A Review

Abstract: Plasma cholesterol levels usually range between 50 and 100 mg/dl at birth, with the cholesterol approximately equally distributed between low-density lipoprotein (LDL) and high-density lipoprotein (HDL). Plasma cholesterol increases rapidly over the first days after birth, predominantly due to an increase in cholesterol with LDL, irrespective of whether the infant is breast fed or fed with infant formulas. With continued feeding, plasma cholesterol becomes progressively, and significantly, higher in infants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Animal studies suggest that early postnatal ingestion of a diet high in cholesterol protects against high-cholesterol challenges later. 112 Low-birth-weight (LBW) premature infants are at risk for stimulation of endogenous cholesterol biosynthesis, resulting in marked elevations in plasma cholesterol as a result of intravenous nutrition. The range, depending on sampling techniques, is 9 to 41 mg/dL.…”
Section: Brain Developmentmentioning
confidence: 99%
“…Animal studies suggest that early postnatal ingestion of a diet high in cholesterol protects against high-cholesterol challenges later. 112 Low-birth-weight (LBW) premature infants are at risk for stimulation of endogenous cholesterol biosynthesis, resulting in marked elevations in plasma cholesterol as a result of intravenous nutrition. The range, depending on sampling techniques, is 9 to 41 mg/dL.…”
Section: Brain Developmentmentioning
confidence: 99%
“…Indeed, preterm newborns have been found to be at risk for marked elevations in plasma cholesterol levels due to upregulation of endogenous cholesterol synthesis. (8) Here, we show that higher early plasma lathosterol levels are associated with higher axial and radial diffusivity, without significant change in ADC or FA, and higher regional volumes in the subcortical white matter. Interestingly, other regions of interest in the white matter, including the posterior limb of the internal capsule and the optic radiations, do not seem to be involved.…”
Section: Discussionmentioning
confidence: 50%
“…(5) In the mature human body, 25% of total body cholesterol content exists in the brain, particularly within myelin. While studies in adults have looked at the relationship between cholesterol levels and brain hemorrhage outcomes(6, 7) and preterm newborns have been shown to be at risk for marked elevations in cholesterol levels due to stimulation of endogenous biosynthesis,(8) there have been no studies addressing the relationship between cholesterol and neurodevelopmental outcomes after preterm birth. This prospective cohort study of preterm newborns uses serial blood samples and brain MRI studies to address the macrostructural (regional brain volumes) and microstructural (diffusion tensor imaging metrics) associations between postnatal cholesterol levels and brain injury and development after preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning cholesterol, some studies showed that dairy lipid-enriched diets could affect the amount of cholesterol in some tissues ( 69 , 70 ). As a result, we showed in this study that plasma cholesterol increased only with DL group, and this is interesting as cholesterol is important during growth and was not provided by VO diets.…”
Section: Discussionmentioning
confidence: 99%